2016
DOI: 10.1175/jas-d-15-0137.1
|View full text |Cite
|
Sign up to set email alerts
|

Stratocumulus Cloud Clearings and Notable Thermodynamic and Aerosol Contrasts across the Clear–Cloudy Interface

Abstract: Data from three research flights, conducted over water near the California coast, are used to investigate the boundary between stratocumulus cloud decks and clearings of different sizes. Large clearings exhibit a diurnal cycle with growth during the day and contraction overnight and a multiday life cycle that can include oscillations between growth and decay, whereas a small coastal clearing was observed to be locally confined with a subdiurnal lifetime. Subcloud aerosol characteristics are similar on both sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 76 publications
4
43
0
Order By: Relevance
“…Chloride (Cl -) and sodium (Na + ) ions are the two largest 10 constituents that were measured in the cloud water and reflect the dominant contribution of sea salt to the cloud-activated aerosol mass in the marine boundary layer, consistent with other studies (Straub et al, 2007;Benedict et al 2012;Wang et al 2016 :Na + mass ratios match reported data for sea water composition (Seinfeld and Pandis, 2016), with good agreement 15 between the probes. A contributing factor for the offset in absolute concentration could stem from differences in the collection of small droplets between the two collectors, since species concentrations often exhibit dependence on droplet size (e.g.…”
Section: Cloud Chemistry Intercomparisonsupporting
confidence: 79%
See 1 more Smart Citation
“…Chloride (Cl -) and sodium (Na + ) ions are the two largest 10 constituents that were measured in the cloud water and reflect the dominant contribution of sea salt to the cloud-activated aerosol mass in the marine boundary layer, consistent with other studies (Straub et al, 2007;Benedict et al 2012;Wang et al 2016 :Na + mass ratios match reported data for sea water composition (Seinfeld and Pandis, 2016), with good agreement 15 between the probes. A contributing factor for the offset in absolute concentration could stem from differences in the collection of small droplets between the two collectors, since species concentrations often exhibit dependence on droplet size (e.g.…”
Section: Cloud Chemistry Intercomparisonsupporting
confidence: 79%
“…Although cloud water sampling for investigating aerosol activation, pollutant transport and chemical evolution now spans several decades, recent 20 measurements have shown skill in promoting linkages between cloud water chemistry and dynamic processes. Examples of this are the characterization of the coupling state of marine clouds with the ocean surface (Wang et al, 2016), the identification of above and below cloud sources (Wang et al, 2016 and the connection with physical properties, such as the presence of giant cloud condensation nuclei . In addition, progress has been made with using cloud water samples to diagnose wet scavenging in marine clouds (MacDonald et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Airborne data relevant to stratocumulus clouds are used from four field experiments based out of Marina, California, using the Center for Interdisciplinary Remotely‐Piloted Aircraft Studies Twin Otter. The first Marine Stratus/Stratocumulus Experiment (MASE‐I) [ Lu et al, ] included 13 flights in July 2005, the second Marine Stratus/Stratocumulus Experiment (MASE‐II) [ Lu et al, ] included 16 research flights in July 2007, the Eastern Pacific Emitted Aerosol Cloud Experiment (E‐PEACE) [ Russell et al, ] included 30 flights between July and August in 2011, and the Nucleation in California Experiment (NiCE) [ Coggon et al, ; Crosbie et al, ] included 23 flights between July and August in 2013.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Navigational, dynamic, and thermodynamic data were obtained from standard instruments described in a number of previous studies (e.g., Crosbie et al, 2016;Wang et al, 2016;Dadashazar et al, 2017). Aerosol particle concentrations were measured using multiple condensation particle counters (CPCs; TSI Inc.), specifically the CPC 3010 (particle diameter, D p > 10 nm) and ultrafine CPC (UFCPC) 3025 (D p > 3 nm).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…More specifically, the predominant sources in the STBL are marine sea spray and biogenic emissions as well as ship exhaust (e.g., Coggon et al, 2014;Modini et al, 2015), while the major sources impacting the FT originate from the continent, including biogenic emissions, wildfires, anthropogenic emissions, and crustal emissions (e.g., Wang et al, 2014;Crosbie et al, 2016). As it is challenging with the current dataset to separate the relative importance of the pollution type affecting the EIL, instead the focus of the subsequent discussion is on aerosol size distributions.…”
Section: Cumulative Vertical Profilesmentioning
confidence: 99%